Structural and surface properties of thermally prepared Ti/RhxTi(1-x)Oy electrodes: I - influence of preparation parameters - De Campos, P. M.; Benedetti, A.; De Faria, L. A.; Cardoso, V; Boodts, JFC (Elsevier B.V., 2002)
Electrodes of RhxTi(1-x) O-y nominal composition were prepared by thermal decomposition of the chloride or nitrate precursor salts dissolved in strongly acidic medium and applied by brush to both sides of a Tidegrees support. A systematic study of the influence of calcination temperature and time as well as oxygen flux was conducted. The coatings were characterised by SEM, EDAX, XRD, open circuit potential measurements and cyclic voltammetry (CV). Visible-ultraviolet spectrophotometry was employed to identify the chemical form of the precursor in solution while thermogravimetric analysis (TGA) was used to assess the decomposition temperature ranges. Optimisation of the coating preparation parameters showed coatings obtained from [Rh(H2O)(6)](NO3)(3) precursor dissolved in HNO3 1:2 (v/v) and fired at 430 degreesC for 2 h in a 5 1 min (-1) oxygen stream-furnished stable electrodes having the highest electrochemically active surface area. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: electrocatalysis; dimensionally stable anodes; rhodium oxide; optimisation; characterisation